Antroponomical toponyms of Mongun-Taiga district - Kara-Sal, Kuder S. (The New Research of Tuva, 2013)
Article represents a competition work at Youth Spiritual Forum "My Land” organized in 2013 by the Dersu Uzala Foundation.